Drinking among college student athletes during the COVID-19 pandemic - Guillot, C. R.; Moore, E. W. G.; Petrie, T. A. (Journal of American College Health, 2024)
Objective: To investigate demographics, sport type, athletic identity, and COVID-19 sport season cancelation in relation to alcohol consumption among college student athletes shortly after the pandemic emerged. Participants: College student athletes recruited from U.S. athletic departments. Methods: Survey data were collected from 5,915 college student athletes in April/May 2020. Results: Being female, Latinx, and in a relationship were associated with lower alcohol consumption. Among males, team sport participation was related to greater alcohol consumption. Among females, athletic identity was inversely related to drinking, which was moderated by sport type, such that alcohol consumption was lower as athletic identity strengthened in individual (vs. team) sport athletes. However, we did not find a relationship of COVID-19 sport season cancelation with drinking. Conclusions: Our gender-specific findings are novel and generalizable based on a large, national sample of college student athletes, and may inform strategies for alcohol consumption education among college team sport athletes.